2019
DOI: 10.1108/dlo-06-2018-0071
|View full text |Cite
|
Sign up to set email alerts
|

Improving business resilience through organizational embeddedness in CSR

Abstract: Purpose The purpose of this paper is to introduce the concept of embeddedness, highlight its connection with corporate social responsibility (CSR) strategies, and argue for its importance in securing and strengthening organizational resiliency. Design/methodology/approach Embeddedness and CSR are both well-researched topics but have been typically addressed on separate literature streams. The paper draws upon this diverse literature to introduce a conceptual framework for embeddedness in CSR. Findings The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 3 publications
3
2
0
1
Order By: Relevance
“…This is because, the organization will be able to forecast any risks that they may be exposed to and plan for them and to take mitigating measures to protect the organization from the said risks. These conclusions are in line with the findings of Lamprinakis (2018) who showed that governance in a strong embedded organization becomes deeply rooted to its natural and socio-economic environments, it is thus able to ably participate in high level CSR activities, that can yield CSR related privileges and hence improving the resilience of a business.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This is because, the organization will be able to forecast any risks that they may be exposed to and plan for them and to take mitigating measures to protect the organization from the said risks. These conclusions are in line with the findings of Lamprinakis (2018) who showed that governance in a strong embedded organization becomes deeply rooted to its natural and socio-economic environments, it is thus able to ably participate in high level CSR activities, that can yield CSR related privileges and hence improving the resilience of a business.…”
Section: Discussionsupporting
confidence: 90%
“…This means that when governance at GDC is improved, the company's business resilience also improves. This finding is consistent with the research conducted by Lamprinakis (2018), who found that strong governance in an organization that is closely integrated with its environment can lead to successful participation in high-level corporate social responsibility (CSR) activities, which in turn can enhance the resilience of the business.…”
Section: Correlation Analysissupporting
confidence: 91%
See 2 more Smart Citations
“…The studies conducted before the pandemic deal with various topics related to the preparedness and organizational reliability theme, such as the significance of emergency planning for enhancing business resilience ( Crichton et al , 2009 ), employee stock ownership and employee governance involvement for boosting resilience ( Lampel et al , 2014 ), and building organizational resilience train through balancing organizational structures ( Andersson et al , 2019 ). We also found studies with an emphasis on corporate social responsibility (CSR) embeddedness ( Lamprinakis, 2019 ) and strategic human resource management ( Al-Ayed, 2019 ), which contribute to organizational resilience.…”
Section: Discussionmentioning
confidence: 88%